Contractual Budgeting And Its Impact On Developing The Structure Of The Government Accounting System In Iraq A Survey Study - Maytham Azeez Khzaee; Yosra Makni Fourati (Harmoni Economics: International Journal of Economics and Accounting, 2024)
This study aims to analyze the implementation of contractual budgeting and its impact on the development of government accounting system structure in Iraq. Amid the challenges facing the public sector in Iraq, the implementation of contract-based budgeting is considered essential to improve transparency, accountability, and efficiency in the management of state finances. This study used a survey approach to collect data from various government agencies in Iraq involved in budget planning and oversight. The results show that although the implementation of contractual budgeting can improve budget management and strengthen the government's accounting system, there are a number of barriers, including a lack of human resource capacity, information technology limitations, and regulatory discrepancies that still exist. This study recommends the need for policy updates and improved training and infrastructure to support the integration of contract-based budgeting in the government accounting structure in Iraq, to ensure the sustainability and effectiveness of public budget management